BE CREATIVE IN GENERATING INCOME, VC URGES YOUNG RESEARCHERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 14 November 2016 – Universiti Sains Malaysia (USM) ViceChancellor Professor Datuk Dr. Asma Ismail today met some 20 young researchers and academicians from the four USM Campuses who have been identified as having the potential to propel the University to the next level at Anjung Jannatun here.